A Canadian Educator Perspective on Quality Perioperative Nursing Practice - Affleck, Dawn (Operating Room Nurses Association of Canada Journal, 2017)
The Perioperative Registered Nurse (PRN) is an essential member of the interdisciplinary surgical team in operating rooms (OR) across Canada. PRNs working in this area need to, given the increased risk of hospital adverse events in the perioperative environment, support and uphold established perioperative nursing principles, guidelines, and standards to protect patients and improve the culture of the environment. This paper is an educator’s exploration of some of the factors that currently influence the ability to deliver quality perioperative nursing care in Canada. Factors such as perioperative education, operating room culture and communication, Canadian perioperative certification, Operating Room Nurses Association of Canada (ORNAC) standards, and the role of senior leadership and administration is examined in detail. Potential strategies and areas for future research, to uphold and maintain quality practice, are identified.